The Development of a Silk Wisdom Database System for Local Development and Creative Tourism Promotion in Maha Sarakham Province - Masaunjik, Nava; Yangkham, Piyawan; Kiangkhwa, Thirasak; Thotham, Amorn; Supat, Thana (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: Silk weaving wisdom is regarded as an important art form and cultural heritage. It encompasses the entire process from cotton cultivation, mulberry planting, silkworm rearing, silk weaving, to processing, and has been passed down from generation to generation, varying across different localities. The purposes of this research were to study and develop the silk wisdom database system for local development and the promotion of creative tourism in Maha Sarakham Province. Methodology: Research using mixed research methods includes research using qualitative research methods. Collecting data from 5 silk manufacturers and 25 customers/tourists, and using a semi-structured interview form as a tool. Results: The respondents emphasized the importance of system design and formatting, user satisfaction, operational efficiency, perceived benefits, perceived ease of use, and attitudes toward system usage. Conclusion: The development of the silk wisdom database system for local development and the promotion of creative tourism in Maha Sarakham Province enables silk producers, customers, and tourists to benefit significantly.